Direct Decay of the Z^0 Boson into Ω_bcc and Ω_bbc Baryons - tawfigh Osati (فیزیک کاربردی ایران)
Electron-positron annihilation experiments are crucial tools for testing the Standard Model due to the simplicity and clarity of the initial state. Several lepton colliders, such as the Electron-Positron Circular Collider, the International Linear Collider, the Future Electron-Positron Circular Collider, and the Muon Collider, are being explored and constructed. One of the possible processes in these colliders is electron-positron annihilation at high energies, processes such as , which is one of the important tools for testing the Standard Model due to the simplicity and clarity of the initial states. In this scenario, heavy quark pairs  are initially produced, which can subsequently directly fragment into heavy baryon pairs  and , respectively. In this paper, the fragmentation functions of heavy quarks b and c into triply heavy baryons and at the first order of perturbation are calculated using pQCD. Then, the branching Fractions of  boson to these baryons,  and , are calculated.